Discovery of (S)-4-isobutyloxazolidin-2-one as a novel leucyl-tRNA synthetase (LRS)-targeted mTORC1 inhibitor. Issue 13 (1st July 2016) - Yoon, Suyoung; Kim, Jong Hyun; Yoon, Ina; Kim, Changhoon; Kim, Sung-Eun; Koh, Yura; Jeong, Seung Jae; Lee, Jiyoun; Kim, Sunghoon; Lee, Jeewoo
Graphical abstract: Abstract: A series of leucinol analogs were investigated as leucyl-tRNA synthetase-targeted mTORC1 inhibitors. Among them, compound5, ( S )-4-isobutyloxazolidin-2-one, showed the most potent inhibition on the mTORC1 pathway in a concentration-dependent manner. Compound5 inhibited downstream phosphorylation of mTORC1 by blocking leucine-sensing ability of LRS, without affecting the catalytic activity of LRS. In addition, compound5 exhibited cytotoxicity against rapamycin-resistant colon cancer cells, suggesting that LRS has the potential to serve as a novel therapeutic target.